2006
DOI: 10.1021/cm061119v
|View full text |Cite
|
Sign up to set email alerts
|

Poly(methacrylic acid)-l-Polyisobutylene:  A Novel Polyelectrolyte Amphiphilic Conetwork

Abstract: For the first time, a reliable procedure for synthesizing new acidic polyelectrolyte-containing amphiphilic conetworks (APCNs), poly(methacrylic acid)-l-polyisobutylene (PMAA-l-PIB), is described. The thorough characterization of the synthesis products is also presented through elemental analysis, differential scanning calorimetry (DSC), and basic swelling studies. Three series of APCNs were successfully synthesized in wide composition ranges by the macromonomer method using exact bifunctional methacrylate-tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 40 publications
2
63
0
1
Order By: Relevance
“…5, it was apparent that by increasing the crosslinking density and the hydrophobic content, the size of the microgels decreased, as anticipated since the crosslinks avert the microgel from expanding. This expected trend, that has been observed before in microgels 4,39 as well as macrogels, 40 was only apparent in high pH solutions in which the AA units were ionised. At lower pH values, the polymer chains of the microgels were not extended, i.e.…”
Section: Microgel Fabrication and Ph Responsiveness Studiessupporting
confidence: 76%
“…5, it was apparent that by increasing the crosslinking density and the hydrophobic content, the size of the microgels decreased, as anticipated since the crosslinks avert the microgel from expanding. This expected trend, that has been observed before in microgels 4,39 as well as macrogels, 40 was only apparent in high pH solutions in which the AA units were ionised. At lower pH values, the polymer chains of the microgels were not extended, i.e.…”
Section: Microgel Fabrication and Ph Responsiveness Studiessupporting
confidence: 76%
“…42,43 Later studies confirmed that the presence of random cross-links frustrates the formation of highly ordered phases, 44 resulting in disordered bicontinuous structures under appropriate conditions. 45,46,47,48 However, these studies have relied on random co-polymerization of monomers with a telechelic macromonomer as a cross-linker, leading to uncontrolled network architectures. 45,46,47,48,49 Furthermore, bicontinuity has most commonly been established through measurements of the swelling ratios in water and non-polar solvents, which can be complicated to interpret due to the possibility for solvent-induced structural rearrangements.…”
mentioning
confidence: 99%
“…P(S-NIPAM-MAA-PEGMA) hydrogel particles exhibit different morphology with central darker parts possibly represents the hydrophobic PS rich segment. The hydrophobic-hydrophobic interactions among PS segments in amphiphilic P(S-NIPAM-MAA-PEGMA) conetwork led to the reorientation of polymer chains forming core-shell type microgels in water [60][61][62][63][64]. Compared to P(S-NIPAM-MAA-PEGMA) hydrogel particles the size of Fe 3 O 4 / SiO 2 /P(S-NIPAM-MAA-PEGMA) composite hydrogel particles decreases after blending with Fe 3 O 4 / SiO 2 nanocomposite particles.…”
Section: Absorption Of Biomoleculesmentioning
confidence: 99%
“…MMA/MAA was added to improve the solubility of styrene in the aqueous dispersion media for facilitating smooth copolymerization with NIPAM as the latter in absence of MMA/MAA may produce larger proportion of water soluble homopolymer due to its comparatively high reaction rate. The hydrophobichydrophobic interactions among hydrophobic PS-PMMA or PS segments in the prepared conetworks are expected to form microgels in water, a phenom-enon generally observed for amphiphilic copolymer networks consisting of hydrophilic and hydrophobic polymer segments [60][61][62][63][64] 4 OH and other chemicals were of analytical grade. Ethanol and deionized water was distilled using a glass (Pyrex) distillation apparatus.…”
mentioning
confidence: 99%